CT pulmonary angiography in lower limb arthroplasty: A retrospective review of 11 249 patients over 11 years. (July 2018) - Karayiannis, P. N.; Hill, J. C.; Stevenson, C.; Finnegan, S.; Armstrong, L.; Beverland, D.
Abstract : Aims: The aims of this study were to determine the indications and frequency of ordering a CT pulmonary angiography (CTPA) following primary arthroplasty of the hip and knee, and to determine the number of positive scans in these patients, the location of emboli and the outcome for patients undergoing CTPA. Patients and Methods: We analyzed the use of CTPA, as an inpatient and up to 90 days as an outpatient, in a cohort of patients and reviewed the medical records and imaging for each patient undergoing CTPA. Results: Out of 11 249 patients, scans were requested in 229 (2.04%) and 86 (38%) were positive. No patient undergoing CTPA died within 90 days. The rate of mortality from pulmonary embolism (PE) overall was 0.08%. CTPA was performed twice as often following total knee arthroplasty (TKA) compared with total hip arthroplasty (THA), and when performed was twice as likely to be positive. Hypoxia was the main indication for a scan, being the indication in 149 scans (65%); and in 23% (11 of 47), the PE was peripheral and unilateral. Three patients suffered complications resulting from therapeutic anticoagulation for possible PE, two of whom had a negative CTPA. Conclusion: CTPA is more likely to be performed following TKA compared with THA. Hypoxia was the main presenting feature of PE. A quarter of PEs which were diagnosed were unilateral and peripheral. Further study may indicate which patients who have a PE after lower limb arthroplasty require treatment, and which can avoid the complications associated with anticoagulation. Cite this article: Bone Joint J 2018;100-B:938–44.